Implementasi Praktik Pembelajaran dan Penguatan Kompetensi Guru melalui Program Magang II di UPT SD Negeri 012 Salo - Nurhaswinda, Nurhaswinda; Husna, Asmaul; Masitoh, Cahya; Lestari, Etika; Aprillia, Astrid; Fitriana, Dana; Aryani, Era; Nania, Resta; Wartina, Sri; Putri, Nurpita; Khairunnisa, Khairunnisa (Universitas Pahlawan Tuanku Tambusai, 2026)
This Community Service activity was carried out based on the results of the second internship program for students of the Primary School Teacher Education Study Program (PGSD) which took place at UPT SD Negeri 012 Salo. This program aims to support the implementation of learning in primary schools while strengthening the pedagogical competencies of teachers and students as prospective educators. This community service was motivated by the school's need for more varied learning assistance, effective classroom management, and the use of learning media that is appropriate to the characteristics of the students. The method of implementation used a participatory descriptive approach, in which students were directly involved in school activities. The stages of the activity included observing the learning process, studying new approaches issued by the government (deep learning approach), learning assistance in the classroom, guided teaching practice, as well as reflection and evaluation of activities. For students, this activity provided real experience in applying learning theory, improving communication skills, classroom management, and professional attitudes as prospective teachers. Overall, the Integrated Internship II program, combined with community service, provides mutual benefits for both the school and the students. This program can serve as an effective education-based community service model in supporting the improvement of learning quality in elementary schools.